2023
DOI: 10.1021/acsomega.2c07326
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Formulations for Better Bioavailability: What We Learned from Clinical Trials Thus Far?

Abstract: Curcumin has been credited with a wide spectrum of pharmacological properties for the prevention and treatment of several chronic diseases such as arthritis, autoimmune diseases, cancer, cardiovascular diseases, diabetes, hemoglobinopathies, hypertension, infectious diseases, inflammation, metabolic syndrome, neurological diseases, obesity, and skin diseases. However, due to its weak solubility and bioavailability, it has limited potential as an oral medication. Numerous factors including low water solubility,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 305 publications
0
45
0
Order By: Relevance
“…In the literature, studies have shown that the combination of curcumin and piperine is not always synergistic or does not always validate the enhancment of curcumin's bioavailability. [36,37] We aimed to evaluate in vitro antibacterial effects of combinations. When we evaluated against the selected bacterial strains, no synergistic effect was observed between curcumin and piperine.…”
Section: Checkerboard Microdilution Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, studies have shown that the combination of curcumin and piperine is not always synergistic or does not always validate the enhancment of curcumin's bioavailability. [36,37] We aimed to evaluate in vitro antibacterial effects of combinations. When we evaluated against the selected bacterial strains, no synergistic effect was observed between curcumin and piperine.…”
Section: Checkerboard Microdilution Resultsmentioning
confidence: 99%
“…However, this effect can vary depending on the organism‘s species and condition. In the literature, studies have shown that the combination of curcumin and piperine is not always synergistic or does not always validate the enhancment of curcumin's bioavailability [36,37] …”
Section: Resultsmentioning
confidence: 99%
“…However, owing to its therapeutic potential, recent advancements in the development of myriad strategies have evolved. Coadministration of piperine, liposomal formulations, nanotechnology‐based delivery systems, development of curcumin‐phospholipid complexes (phytosomes), and hydrogel delivery systems (Hegde et al, 2023). These innovative approaches exhibit a promising role in augmenting the bioavailability of curcumin.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin is a constituent of turmeric that is endowed with multiple pharmacological actions, some of which are of clinical relevance (Hassanzadeh et al, 2020; Hegde et al, 2023; Heidari et al, 2022; Kumar et al, 2021; Mohajeri & Sahebkar, 2018; Mokhtari‐Zaer et al, 2018; Momtazi‐Borojeni et al, 2018; Parsamanesh et al, 2018; Soltani et al, 2021). Curcumin has been reported to be efficacious in the treatment of many skin conditions including eczema, acne, wounds, wrinkles, and scabies (Aggarwal et al, 2007; Bhagavathula et al, 2009; Gopinath et al, 2004; Jagetia & Rajanikant, 2004; Panahi et al, 2019; Phan et al, 2006).…”
Section: Discussionmentioning
confidence: 99%